Implementation simulink modeling to analysis the transient cases and torque speed characteristic in a three phase induction motors - Omar Al-barbarawi; Ghazi M. Qaryouti (Institute of Advanced Engineering and Science, 2019)
In this research, has been a developed modular approach for investigation of the dynamic behavior and analysis the steady -state and transient cases for a three-phase induction motor when it is fed with a balanced and unbalanced voltage , and analysis the behavior of the Torque-Speed characteristics at various conditions. This analysis is done systematically by development two mathematically models. Where the first model is proposed to simulate the dynamic behavior of the motor when supplying it at balanced and unbalanced voltage in Matlab/Simulink by using d-q axis theory in the reference frame. This model can investigate and described in details the behavior of the induction motor parameters, and enables the researcher to calculate or investigate any variable for an induction machine parameter ; (e.g. The voltage, current, flux, speed and torque as a function of time) in both cases transient and steady state , when the motor in operation state [11-16]. The other model is proposed to simulate in the Microsoft Excel program, by using the ratio between the conventions of the electromagnetic torque equation(Tem) and maximum torque equation (Tmax) . To study and analysis the behavior of the Torque-Speed characteristics for a 3-phase induction motor. Where this models study's by using Excel program's and Matlab / Simulink to simulation the effect of the various parameters on the dynamic behavior of the motor such as inserting variable external resistance in series with rotor circuit , and when supplying the stator by variable voltage. These Mathematical models could be used for a wide range of motors which has a various horse powers , which needing it in a scientific research and practical applications.